2021
DOI: 10.1002/mc.23378
|View full text |Cite
|
Sign up to set email alerts
|

Tumor‐derived exosomes: Key players in non‐small cell lung cancer metastasis and their implication for targeted therapy

Abstract: Exosomes represent extracellular vesicles of endocytic origin ranging from 30 to 100 nm that are released by most of eukaryotic cells and can be found in body fluids. These vesicles in carrying DNA, RNA, microRNA (miRNA), Long noncoding RNA, proteins, and lipids serve as intercellular communicators. Due to their role in crosstalk between tumor cells and mesenchymal stroma cells, they are vital for tumor growth, progression, and anticancer drug resistance. Lung cancer is a global leading cause of cancer‐related… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 132 publications
0
9
0
Order By: Relevance
“…Recent studies have demonstrated that both cellular and exosomal microRNAs regulate the expression of genes that play essential roles in cancer cell migration, invasion, and metastasis [ 13 , 14 ].…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies have demonstrated that both cellular and exosomal microRNAs regulate the expression of genes that play essential roles in cancer cell migration, invasion, and metastasis [ 13 , 14 ].…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, TEV secretion constitutes a large portion of the formation of the tumor microenvironment and drug resistance, especially during excessive stress when the secretion is substantially increased. 37…”
Section: Ev Significance To Cancermentioning
confidence: 99%
“…177 Additionally, the RNA and miRNA cargo of TEVs play an especially crucial role in antitumor responses and, therefore, remain an important research topic for potential therapeutic intervention. 37 TEVs have been shown to elicit antitumor responses through direct activation of immune cells by transference of certain miRNA during cellular uptake. 178,179 One study reveals how the delivery of tumor derived exosomal miR-130 can direct the polarization of macrophages to inhibit tumor invasion.…”
Section: Evs In Immunotherapymentioning
confidence: 99%
“…Moreover, in lung cancer, gefitinib (Iressa), an anticancer drug that inhibits the epidermal growth factor receptor (EGFR), was shown to increase the intracellular translocation of exosomes, but decrease that of liposomes, which are typically used for drug-delivery systems [ 309 ]. In addition, compared to liposome-encapsulated doxorubicin, exosome-encapsulated doxorubicin results in robustly higher anticancer activity against non-small cell lung cancer [ 310 , 311 ]. Furthermore, degradation of the exosomal membrane proteins further enhanced intracellular migration induced by gefitinib treatment [ 304 ]; thus, exosomal membrane lipids may contribute to the promotion of intracellular translocation during gefitinib treatment.…”
Section: Ev Uptake In Target Cells Via Macropinocytosismentioning
confidence: 99%